2018
DOI: 10.4103/0366-6999.235878
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dandelion Extract on the Proliferation of Rat Skeletal Muscle Cells and the Inhibition of a Lipopolysaccharide-Induced Inflammatory Reaction

Abstract: Background:Dandelion is commonly used in traditional Chinese medicine with several active compounds found in extracts. It has a variety of pharmacological effects, such as a reduction in swelling and inflammation, and detoxification. The mechanism by which dandelion extract inhibits the inflammatory response in skeletal muscle cells remains unknown; therefore, the aim of this study was to investigate the effects of dandelion extract root on the proliferation of skeletal muscle cells and the alleviation of lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…The methanolic extract was evaporated by rotary evaporator to obtain a semisolid mass, which was stored at −20°C until needed. 17 …”
Section: Methodsmentioning
confidence: 99%
“…The methanolic extract was evaporated by rotary evaporator to obtain a semisolid mass, which was stored at −20°C until needed. 17 …”
Section: Methodsmentioning
confidence: 99%
“…Notably, LPS is widely used to induce sepsis by initiating hyperactivation of the inflammatory response, [ 20 22 ] which was utilized in this study to establish the septic model in rats, as well as in H9C2 and HK-2 cells. First, we observed that the levels of cTnI, CK-MB, BUN, and Cr were increased in rat serum.…”
Section: Discussionmentioning
confidence: 99%
“…[ 51 ] It is well known that Wnt is an essential pathway for the regulation of cell proliferation and myogenesis. [ 52 , 53 ] As an element in the Wnt pathway, the expression of Pitx2 is up-regulated by electrical stimulation in the muscle of rats with spinal cord transection. The activation of Wnt induced by electrical simulation is also found in neural stem/progenitor cells [ 54 , 55 ] and cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%